Pengaruh Tingkat Percaya Diri CEO terhadap Risiko Penurunan Harga Saham dengan Efisiensi Investasi sebagai Mediasi - Yusuf, Nila Hiliyah (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p07, 2021)
CEO has a role to make investment decisions. Age, education and work experience are factors can effect the CEO's confidence level to making decisions. When the investment decisions biased and risk lowering the company's performance, there will be a CEO's decision to delay bad information. Long delays bad information will increase stock price crash risk on future. Therefore, the purpose of this study is to examine the effect of the CEO's confidence level on future stock price crash risk with investment efficiency as a mediation. The manufacturing sector is used as the object of research with 98 companies as research samples with a research period from 2011-2019. Path analysis was used as an analytical technique and Sobel test as a measure of mediation. The results of this study prove that investment efficiency is able to mediate the effect of CEO's confidence level on future stock price crash risk. Keywords: CEO's Confidence Level; Investment Efficiency; Future Stock Price Decrease Risk.